Primary Cutaneous CD30-Positive Large T-Cell Lymphoma in an 80-Year-Old Man: A Case Report. (22nd March 2011) - Hussain, Rehan; Bajoghli, Amir
Abstract : Primary cutaneous CD30-positive large cell lymphoma (CD30+ PCLCL) is a rare subtype of cutaneous T-cell lymphoma (CTCL) that can present in a variety of ways. We report a patient with a three-month history of an enlarging, exophytic mass with two smaller satellite lesions on the left forearm. Biopsy of the skin stained positive for CD30, and, after thorough systemic evaluation, a diagnosis of CD30+ PCLCL was made. When PCLCL is suspected, it is important to perform immunohistological studies for CD30 types and conduct a thorough workup to rule out systemic LCL. These measures will reduce the use of unnecessarily aggressive chemotherapy regimens for CD30+ PCLCL, an indolent disease with a favorable prognosis.